ЗМІ та деякі проблеми поліетнічності в російській столиці - Малькова, В. (Народна творчість та етнографія, 2010)
В статье рассматриваются современные проблемы межэтнического общения коренных москвичей, русских и приезжих других национальностей. Автор, анализируя факты, идеологемы и мифологемы, комментарии, особые лексические формы в печатных СМИ, затрагивает много проблем в организации жизни большого полиэтнического мегаполиса. The article shows the modern problems of the interethnical communication between the natives of Moscow, the Russians and the other ethnically different new-comers. Analyzing the facts, ideologems and mythologems, commentaries and specific lexical forms in the mass-media the author puts a lot of issues concerning the organization of the megalopolis polyethnical life.